Enhanced Photocurrent in PbS Quantum Dot Photovoltaics via ZnO Nanowires and Band Alignment Engineering. Issue 24 (2nd September 2016) - Rekemeyer, Paul H.; Chang, Sehoon; Chuang, Chia‐Hao Marcus; Hwang, Gyu Weon; Bawendi, Moungi G.; Gradečak, Silvija
Abstract : Lead sulfide quantum dot (QD) solar cells employing an ordered bulk heterojunction with ZnO nanowires and band alignment engineering of the QD film achieve photocurrent density greater than 30 mA cm −2, the highest reported for a QD photovoltaic (PV) device with an ideal band gap of 1.3 eV. This record performance is shown to be the result of simultaneous improvement in light harvesting and carrier collection efficiency, and these effects are generalizable to other PV absorber materials.